Examining the utilization of participatory research with autistic youth in mainstream/public schools: a scoping review - Newson, Alexandra; Quinn, Sarah; Nese, Rhonda N. T. (Frontiers in Education, 2024)
Purpose: This scoping review explores the utilization of participatory research with autistic youth in K-12 public/mainstream school settings.A scoping review was performed to identify how often participatory research methodologies are used in K-12 public/mainstream school settings with autistic students, what researchers report are the strengths, barriers, and recommendations in using participatory research methodologies with autistic students in K-12 public school settings and what type of demographic information is included in the studies.Results: Five studies were included for review focusing on participatory research with autistic youth in K-12 public or mainstream school settings. The studies used a range of participatory research methodologies to explore the experiences of mainly male autistic youth in the UK and Australia. Strengths, challenges, and recommendations noted included opportunities for empowerment, increased ownership, issues with teachers, thinking critically about communication, and collaboration with partners.Participatory research with autistic school-aged youth is an emerging practice. This is evidenced by the small number of studies included in this review. The findings highlight concerns about the lack of representation of autistic females and students with historically marginalized racial identities in autism research. Recommendations for including these groups in autism research, implications, and limitations are discussed.